Антология выдающихся достижений в науке и технике. Часть 35: Лауреаты Нобелевской премии по физике за 1990-1994 гг. - Баранов, Михаил Иванович (НТУ "ХПИ", 2016)
Приведен краткий аналитический обзор выдающихся научных достижений ученых мира, отмеченных Нобелевской премией по физике за период 1990-1994 гг. В число таких достижений вошли результаты пионерских исследований по рассеянию релятивистских электронов на протонах и нейтронах, открытие сходств физики твердой материи и физики конденсированного состояния вещества, создание революционного детектора элементарных частиц, открытие новых пульсаров и новые возможности в изучении гравитации, создание нейтронной спектроскопии и метода нейтронной дифракции.

Purpose. Implementation of brief analytical review of the distinguished scientific achievements of the world scientistsphysicists, awarded the Nobel Prize in physics for period 1990-1994. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information of world level in area physics of elementary particles, physics of high energies, of astrophysics, of modern theoretical and experimental physics. Results. The brief analytical review of the scientific openings and distinguished achievements of scientistsphysicists is resulted in area of modern physical and technical problems which were marked the Nobel Prize in physics for period 1990-1994. Originality. Systematization is executed with exposition in the short concentrated form of the known scientific and technical materials, devoted pioneer researches results on dispersion of relativism electrons on protons (neutrons), to opening of likenesses of physics of hard matter and physics of the condensed state of matter, creation of revolutionary detector of elementary particles, to opening of new pulsars and new possibilities in the study of gravitation, to creation of neutron spectroscopy and method of neutron diffraction. Practical value. Popularization and deepening of scientific and technical knowledges for students, engineer and technical specialists and research workers in area of modern theoretical and experimental physics, extending their scientific range of interests and cooperant further development of scientific and technical progress in human society.
An anthology of the distinguished achievements in science and technique. Part 35: Nobel Prize Laureates in Physics for 1990-1994
Keywords: современная физика; рассеяние релятивистских электронов на тяжелых частицах; физика твердой материи и конденсированного состояния; мультиэлектродный детектор элементарных частиц; новые пульсары и гравитация; нейтронная спектроскопия; дифракция; modern physics; achievements; dispersion of relativism electrons on heavy particles; physics of hard matter and condensed state; multielectrode detector of elementary particles; new pulsars and gravitation; neutron spectroscopy and diffraction